The psychophysiological influence of exertion and affect on sport-specific cognitive and physical performance - Davis, P. A.; Sörman, D.; Carlberg, A.; Rognsvåg, E.; Stenling, A. (Journal of Science and Medicine in Sport, 2022)
Objectives: The purpose of the present study was to examine differences in cognitive and physical performance, affective states, perceived exertion, and physiological responses between trials with cognitive, physical, or combined cognitive and physical load. Design: Randomised cross-over trial. Methods: Highly trained competitive orienteers (n=15 men; n=10 women) completed three randomised trials comprised of: (1) sport-specific cognitive tests; (2) 35-minute cycling time trial; and (3) combined sport-specific cognitive tests and 35-minute cycling time trial. Measures taken during the trials recorded affective states, perceived exertion, heart rate, blood lactate, cycling watts, as well as working memory, updating, planning and decision making. Results: No significant differences in cognitive performance accuracy were observed within or across trials although reaction times improved within trials and were fastest in the combined trial. Blood lactate, heart rate, perceived exertion, negative affective states, and watts were highest in the physical trial. Conclusions: The combined load of undertaking sport-specific cognitive tests and a cycling time trial did not influence cognitive performance accuracy. Athletes produced greater watts when completing the physical task independently compared with the combined trial, however psychophysiological responses were worse. Further investigation is warranted to determine whether athletes' attentional focus underpins psychophysiological responses to dual-task sport performance.